SENYAWA FITOKIMIA DAN AKTIVITAS ANTI COVID STUDI IN SILICO EKSTRAK CABE JAWA (Piper retrofractum Vahl) - Umarudin, Umarudin; Syafitri, Meyke Herina; Aristyawan, Andhika Dwi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Javanese chili has the potential to develop, one of which is that it contains phytochemical compounds and essential oils, which can act as antioxidants in preventing COVID-19, so it is necessary to utilize the natural potential in Indonesia, namely Javanese chili. This research aims to determine the phytochemical screening and anti-covid activity of an in silico study of Javanese chili extract. This research method carried out phytochemical screening of ethanol extracts, tested for alkaloids, flavonoids, tannins, saponins, and terpenoids, tests for determining levels of piperine, essential oils, and cavitsin, as well as in silico studies with piperine ligands with RdRP and ACE2 receptors docked with Hex.8.0.0 and visualized with discovery studio. This research shows that the phytochemical screening results of Javanese chili fruit extract are positive for containing alkaloids, flavonoids, tannins, saponins, terpenoids, piperine 3.36%. This research concludes that in silico, the Javanese chili piperine compound can bind to the active site of ACE Sarcov 2 through RdRP inhibition.